2021
DOI: 10.3390/en14175524
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Key Enabling Technologies in the Nearly Zero Energy Buildings Monitoring, Control and Intelligent Management

Abstract: The 2018 revision of the European Performance Building Directive (EPBD) requires that from the year 2020 onwards, all new buildings will have to be “nearly zero energy buildings”. It also further promotes smart building technologies, raising awareness amongst building owners and occupants of the value behind building automation. The European Commission also identified, in 2011, Key Enabling Technologies (KETs), which provide the basis for innovation in the EU. In the frame of the SUDOKET project, the Solar XXI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Another aspect that must be considered is the symbiotic relationship of architecture's passive components and active systems to target the optimal indoor environmental conditions. In this way, Lourenço et al [40], in the near-zero Solar XXI building, located in Lisbon, Portugal, assessed with EnergyPlus software the integration of optimized passive architecture solutions (vents above the door frame, earth tubes, adjustable blinds, thermal mass construction) and active systems (south facade building integrated photovoltaic, lighting sensors), together with building control and monitoring technologies. The authors concluded that intelligent buildings with automated control systems display better performance dealing with indoor thermal comfort, air quality, and illumination.…”
Section: Operation Guidelinesmentioning
confidence: 99%
“…Another aspect that must be considered is the symbiotic relationship of architecture's passive components and active systems to target the optimal indoor environmental conditions. In this way, Lourenço et al [40], in the near-zero Solar XXI building, located in Lisbon, Portugal, assessed with EnergyPlus software the integration of optimized passive architecture solutions (vents above the door frame, earth tubes, adjustable blinds, thermal mass construction) and active systems (south facade building integrated photovoltaic, lighting sensors), together with building control and monitoring technologies. The authors concluded that intelligent buildings with automated control systems display better performance dealing with indoor thermal comfort, air quality, and illumination.…”
Section: Operation Guidelinesmentioning
confidence: 99%
“…They showed that the total energy consumption of heating, ventilation, and air conditioning in smart buildings could be reduced by around 28% and electricity cost could be cut by around 19.6% [52]. Additionally, Lourenço et al [53] demonstrated that with the use of key enabling technologies such as building-integrated photovoltaic, earth tubes, and intelligent automatic system control, it is possible to significantly reduce heating energy consumption by 22% in a yearly basis. With respect to the identification of two SBMS attribute categories for commercial buildings namely "intelligent building operations" and "safety & recovery readiness", they pointed to the purpose of cultivating SBMS attributes at the conceptual level.…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%
“…Jazizadehet et al [25] have shown the potentials of integration of diffuser-level adaptive actuation with improvements in thermal comfort satisfaction and energy savings of around 25%. Recently, the role of the key enabling technologies has been experimentally verified by Lourenço et al [26]. Moreover, Kalaimani et al [27] have shown how energy use could be reduced during periods of low occupancy by choosing appropriate thermal setpoints.…”
Section: Introductionmentioning
confidence: 99%